(untitled) (Global Journal of Science Frontier Research, 2020)
Hot pepper is one of the most important vegetables and spice crops cultivated in many parts of the country. Despite its economic, nutritional, and medicinal purposes, the research done so far on this crop is very limited. Therefore, the current research was conducted to identify best hot pepper variety for pod yield and quality and determine optimum rates of nitrogen (N) fertilizer for hot pepper production in Wolaita, Southern Ethiopia. The field experiment was laid out in a randomized complete block design (RCBD) with three replications. Four varieties (Melka Awaze, Melka Shote, Avpp0514, and Avpp0206 with four N fertilizer rates (0, 50, 100, and 150kg N ha-1) were assigned to the experimental plot with a total of 16 treatments. The result showed that interaction of variety and rates of N fertilizer significantly (P < 0.05) affected plant height, leaf area, leaf area index, total pod yield, marketable pod yield and significantly (P < 0.001) affected pod length, pod width, pod wall thickness and disease incidence of hot pepper. The highest marketable pod yield (16.33 t ha-1) was achieved from variety Avpp0514 coupled with the rate of 100 kg N ha-1 followed by variety Avpp0514 at the rate of 50 kg N ha-1 (14.93 t ha-1) whereas the lowest pod yield was achieved from variety Melka Shote at 0kg N ha-1. The highest oleoresin content (25.89%) was recorded by Avpp0514 at 50 kg N ha-1.